Reviewing the concept of design frames towards a cognitive model. (12th December 2022) - Kelly, Nick; Gero, John S.
Abstract: This paper critically reviews literature about design framing to clarify an understanding of what is meant by the construct of a design frame. It describes the origins of the term design frame and characterises three distinct definitions that can be found within the literature. It reviews empirical studies of design framing to highlight definitional confusion between studies. It discusses the significance of Dorst's propositional model of design frames and juxtaposes design frames with other related constructs. It clarifies ways that the resolution of nomenclature for describing design framing might lead to a more coherent body of empirical research into this topic. It suggests that there is value in developing a better cognitive model of design framing and outlines potential steps towards such a model.